Effects of peppermint (Mentha piperita L.) oil in cardiometabolic outcomes in participants with pre and stage 1 hypertension: Protocol for a placebo randomized controlled trial - Jonathan Sinclair; XuanYi Du; Gareth Shadwell; Stephanie Dillon; Bobbie Butters; Lindsay Bottoms (PLoS ONE, 2025)
Background Hypertension is the predominant risk factor for cardiovascular disease morbidity and mortality, with significant healthcare utilization and expenditure. Pharmaceutical management is habitually adopted; although its long-term effectiveness remains ambiguous, and accompanying adverse effects are disquieting. Peppermint owing to its abundance of menthol and flavonoids, possesses a range of potential hypertensive benefits. Rationale Our previous trial has shown that peppermint is able to mediate significant improvements in systolic blood pressure in healthy individuals. But there has yet to be any randomized placebo-controlled studies, examining the efficacy of peppermint supplementation in hypertensive individuals. Objective This study proposes a placebo randomized controlled trial, exploring the effects of daily peppermint oil supplementation on outcomes pertinent to hypertensive disease in individuals with pre and stage 1 hypertension. Methods and analyses This 20-day, parallel randomized, placebo-controlled trial will recruit 40 individuals, assigned to receive either 100μL per day of either Peppermint oil or a peppermint flavoured placebo. The primary trial outcome will be the between-group difference in systolic blood pressure from baseline to post-intervention. Secondary outcome measurements will be between-group differences in anthropometric, haematological, diastolic blood pressure/ resting heart rate, psychological wellbeing, and sleep efficacy indices. Statistical analysis will be conducted on an intention-to-treat basis using linear mixed effects models to contrast differences in the changes from baseline to 20-days between the two trial arms. Ethics and dissemination Ethical approval has been granted by the University of Central Lancashire (HEALTH 01074) and the study has formally been registered as a trial (NCT05561543). Dissemination of the trial findings will be through publication in a peer-reviewed journal. Trial registration ClinicalTrials.gov NCT05561543. Ethics HEALTH 01074.